Evaluation, a Challenge for Successful Management of the Public Administration - Lako, Marjana; Dumi, Alba (Mediterranean Journal of Social Sciences, 2012)
The evaluation of individual performance has always been an element for the motivation of the employees of the public administration and the increase of its performance. In this study there are efforts done to point out some problems of the evaluation of individual performance as a part of the organization’s culture, which affects the increase of efficiency and consists of the key for a successful management of the public administration. The concept of evaluation must be considered as a psycho-social and administrative process which has its own impacts on the motivation and performance of the public administration. The right relations between them, increase of the evaluation criteria, the combination of the evaluation of individual performance with the respective structure as a strong bond of evaluation and career, use of the method of self-evaluation, evaluation for your superior and your colleague, financial rewards etc, are not only the success of the administration but also guarantee a qualitative management.